2013
DOI: 10.1097/ico.0b013e31826ef43b
|View full text |Cite
|
Sign up to set email alerts
|

Management and Outcomes of Descemet Stripping Automated Endothelial Keratoplasty With Intraocular Lens Exchange, Aphakia, and Anterior Chamber Intraocular Lens

Abstract: In comparison with uncomplicated DSAEK cases, higher graft and IOL dislocations were observed in cases involving IOL exchanges, ACIOLs, or aphakia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…Endothelial cell loss of about 19.6% 3 months after surgery from eye bank values is relatively low, and it compares favourably with the values reported after DSAEK and IOL exchange or even after uncomplicated DMEK procedure; but longer follow-up is needed 7 13 15…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Endothelial cell loss of about 19.6% 3 months after surgery from eye bank values is relatively low, and it compares favourably with the values reported after DSAEK and IOL exchange or even after uncomplicated DMEK procedure; but longer follow-up is needed 7 13 15…”
Section: Discussionsupporting
confidence: 67%
“…Hsu et al 15 reported a series of 30 complicated DSAEK eyes with a mean follow-up of 20.3 months. Of the 14 eyes who had undergone concurrent IOL exchange with DSAEK only one sulcus lens was placed.…”
Section: Discussionmentioning
confidence: 99%
“…1-3 Post-operative dislocation of the donor endothelial graft remains one of the most common complications of DSAEK with a mean reported rate of 14% but with large variation between studies. 1,2,4-8 Recipient factors including previous incisional glaucoma surgery, 9,10,11 previous penetrating keratoplasty, 12 aphakia, 13,14 prior vitrectomy, 15 and the presence of an anterior chamber intraocular lens 16 have been shown to increase the rate of donor dislocation. Treatment of graft dislocation often requires a rebubble procedure, in which sterile air is injected into the anterior chamber to promote graft adherence, 7 which may increase the risk of endothelial failure.…”
Section: Introductionmentioning
confidence: 99%
“…DSAEK shows the best outcomes when performed in phakic or pseudophakic eyes with diseased endothelium,[ 19 ] as surgery in aphakic, vitrectomized eyes, carries a high risk of lenticule detachment/dislocation, and primary graft failure because of inadequate air tamponade. [ 19 20 ] This explains the preference for PKP in aphakic eyes over DSAEK.…”
Section: Discussionmentioning
confidence: 99%